Cytotoxic, Membrane Stabilizing and Anti-diarrheal Activities of Bambusa bambos Linn. (Bangladesh Pharmaceutical Journal, 2016)
Bambusa bambos Linn., a herbal medicine belonging to the family Poaceae, is locally known as Kanta bans or only bans. The crude methanolic extract of leaves of B. bambos and its different partitionates were evaluated for in vitro cytotoxicity, membrane stabilizing and anti-diarrheal activities. In the cytotoxicity screening, the dichloromethane and pet ether soluble fractions displayed the highest lethality to brine shrimps with LC50 of 3.91 and 8.45?g/ml, respectively, whereas the standard vincristine sulphate had LC50 value of 0.45?g/ml. In the membrane stabilizing assay, the crude methanolic extract exhibited highest inhibition of haemolysis of human RBCs by 71.08 ± 0.43% and 49.44 ± 0.73% in heat- and hypotonic solution-induced haemolysis, respectively. The extract exhibited significant (p < 0.05) anti-diarrheal effect at a dose of 400 mg/kg body weight in the castor oil induced anti-diarrheal assay.Bangladesh Pharmaceutical Journal 19(2): 161-165, 2016